THE USE OF OF DIGITAL MARKETING TOOLS IN ADVERTISING MANAGEMENT - DRONOVA, Tetiana; KHURDEI, Viktoriia; MISHCHENKO, Dmytro; PAVLOVSKA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Modern advertising management is largely dependent on innovative technologies. They provide the ability to personalize advertising, automate processes, improve the efficiency of analytics and forecasting, create new forms of interaction with consumers, and rationalize the use of resources. Companies that actively integrate these technologies gain significant competitive advantages and can successfully develop their business in today's dynamic environment.The article defines the concept of "advertising management", which covers planning, organization, implementation and control of advertising campaigns with a view to effective promotion of products or services on the market. The conditions for the formation of modern advertising management, including the impact of globalization, the development of information technology and changes in consumer behavior, are considered. The reasons for the crucial importance of digital marketing for any business in the new century are characterized. Digital marketing allows you to measure the results of advertising campaigns in real time, ensuring cost-effectiveness through accurate targeting and cost optimization. The flexibility of digital platforms allows you to quickly adapt advertising strategies to changes in the market, and automatic optimization of platforms simplifies the management of advertising campaigns. Digital marketing creates a space for creative storytelling, allowing brands to tell their stories through interactive and visually appealing formats. In addition, it promotes a deep understanding of customers by analyzing their behavior and preferences. The article describes digital marketing tools that contribute to the successful implementation of advertising activities. They include artificial intelligence, augmented reality (AR) and virtual reality (VR), chatbots, Internet of Things (IoT), voice assistant, programmatic advertising, content marketing, personalization, big data and machine learning (ML), mobile advertising, mobile applications.
Keywords: advertising management; digital marketing; digital marketing tools; innovative technologies